(untitled) (Annual of the Faculty of Philosophy in Skopje, 2018)
In the modern society many factors influence the societal processes. There is no social sphere that can remain untouched by the changes that happen every single day. Besides all the specifics of modern lifestyle, a particular one is the religion as one of the most complex societal phenomena. The modern sociologists of religion share the opinion that in the 21st century as well, in the era of globalization and internet-revolution, the religion is not just losing its path, but is becoming even more established in the societal environment. In the context of religion, the emphasized moral aspects are very significant, especially those of the dominant monotheistic religions (Judaism, Christianity and Islam) as universal human moral values. By accepting these values, a person enriches himself.